Method of straw ditch-buried returning, development of supporting machine and analysis of influencing factors - Tang, Han; Xu, Changsu; Xu, Wenlong; Xu, Yanan; Xiang, Yushun; Wang, Jinwu (Frontiers in Plant Science, 2022)
This paper aims to solve the problems of the low quality and shallow depth of the traditional straw return method. According to the requirements of the new furrow burial and return agronomic model, a corn straw ditch-buried returning machine was designed that could complete the processes of picking, conveying, ditching, soil-covering and pressing simultaneously. Key components were theoretically analyzed and designed, such as the pickup device, ditching device and straw-guiding soil-covering and pressing device. Based on a field experiment, the main factors influencing the effects of straw picking, soil ditching and straw return were studied. Both the forward speed and pickup device speed imposed significant effects on the straw picking rate. The ditching area, ditching width consistency factor and ditching depth stability factor gradually decreased with increasing forward speed and gradually increased with increasing trenching device speed. There occurred significant interaction between the forward speed, pickup device speed and ditching device speed. At a forward speed of 1.68 m/s, the picking device speed reached 330 r/min, the ditching device speed was 290 r/min, and the highest straw return rate reached 93.65%.